Juvenile Residential Facility Census, 2000-2010 -- Concatenated Data (United States) ([Verlag nicht ermittelbar], 2012)
The Juvenile Residential Facility Census (JRFC) collected basic information on facility characteristics, including size, structure, security arrangements, and ownership. It also collected information on the use of bedspace in the facility to indicate whether the facility was experiencing crowding. The JRFC included questions about the type of facility, such as detention center, training school, ranch, or group home. This information was complemented by a series of questions about other residential services provided by the facility, such as independent living, foster care, or other arrangements. JRFC used four modules to collect information on the physical health services, educational services, substance abuse treatment, and mental health treatment provided to youth in these facilities. These four modules were not always collected each year. While not evaluating the effectiveness or quality of these services, the JRFC gathered important information about the youth the services were directed toward and how the services were provided. The census indicated the use of screenings or tests conducted to determine counseling, education, health, or substance abuse needs, and also examined prominent issues about conditions of confinement, including the restraint of youth and improper absences from the facility. The JRFC has been administered biennially since 2000, in even-numbered years. The census reference date is the fourth Wednesday in October.